Challenges in implementing occupational health and safety in Indian information and communication technology industry - Mittra, Gaurav; Rahul, Manmohan; Mehta, Gitanjali (Intelektual Pustaka Media Utama, 2025)
An organization's safety culture encompasses the values, perceptions, attitudes, and behaviors of its members. This culture forms a shared bond among individuals within the organization, influencing every facet of life. As a result, the safety ethos of a company plays a crucial role in nurturing a more expansive safety culture in society. Key components of a safety culture include leadership commitment, occupational health and safety (OHS) policies, meticulous planning, resource management, active participation across all levels, seamless integration, regular review processes, well-defined procedures, comprehensive documentation, and effective risk management. The amalgamation of these elements contributes to cultivating a work environment where prioritizing workplace safety becomes paramount. This commitment not only enhances the safety of the workplace but also addresses a crucial aspect of social sustainability, directly linked to human well-being. This study investigates the correlation between the successful execution of an occupational health and safety management system (OHSMS) and the level of involvement of both internal and external stakeholders in promoting safety practices within the organization, evaluates the mediation effect of work engagement and social sustainability on OHSMS implementation and safety behavior and examines the safety standards and actual implementation of these standards in information and communication technology (ICT) industry in India.